Intraductal/ductal histology and lymphovascular invasion are associated with germline DNA‐repair gene mutations in prostate cancer - Isaacsson Velho, Pedro; Silberstein, John L.; Markowski, Mark C.; Luo, Jun; Lotan, Tamara L.; Isaacs, William B.; Antonarakis, Emmanuel S. (The Prostate, 2018)
Background Germline mutations in genes mediating DNA repair are common in men with recurrent and advanced prostate cancer, and their presence may alter prognosis and management. We aimed to define pathological and clinical characteristics associated with germline DNA‐repair gene mutations, to facilitate selection of patients for germline testing. Methods We retrospectively evaluated 150 unselected patients with recurrent or metastatic prostate cancer who were offered germline genetic testing by a single oncologist using a clinical‐grade assay (Color Genomics). This platform utilizes next‐generation sequencing from saliva to interrogate 30 cancer‐susceptibility genes. Presence or absence of a deleterious germline mutation was correlated with histological and clinical characteristics, and with family history of cancer. All patients with DNA‐sequence alterations (pathogenic or variants) were offered genetic counseling. Results Between July 2016 and July 2017, 150 consecutive patients underwent germline testing; pathogenic mutations were identified in 21 men (14%). Among those with germline mutations, 9 (43%) were in BRCA2, 3 (14%) were in ATM, 3 (14%) were in CHEK2, and 2 (9%) were in BRCA1. While there were no associations between germline mutations and age, tumor stage, Gleason sum or family history; mutation‐positive patients had lower median PSA levels at diagnosis (5.5 vs 8.6 ng/mL, P = 0.01) and unique pathologic features. Namely, men with germline mutations were more likely to harbor intraductal/ductal histology (48% vs 12%, P < 0.01) and lymphovascular invasion (52% vs 14%, P < 0.01). Finally, 44% of patients with a positive germline test would not have been offered genetic screening according to current National Comprehensive Cancer Network (NCCN) guidelines. Conclusions Presence of intraductal/ductal histology and lymphovascular invasion appear to be associated with pathogenic germline DNA‐repair gene mutations in men with prostate cancer, and identification of these features may help to select patients for germline testing. NCCN guidelines may be inadequate in predicting which prostate cancer patients should undergo genetic screening.